Enhancing Students’ Academic Performance by Organizational Development Interventions- A Case Study in the College of Bioengineering of Beijing Polytechnic - Xie, Guoli; Lu, Lee Hsing (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
The primary objective of this study is to use OD interventions to improve higher vocational students’ academic self-efficacy, perceived teacher support, and peer relationship to improve their academic performance, with learning engagement as the mediating variable. The study was conducted on sixty first-year Beijing Polytechnic Bioengineering Department students using qualitative and quantitative research methods. Before implementing the OD intervention, the researcher collected data on academic self-efficacy, perceived teacher support, peer relationship, learning engagement, and academic performance through questionnaires and interviews. The OD interventions included goal setting, feedback, coaching, team building, appreciative inquiry, and team activities. After the intervention, the same questionnaires and interviews were used to gather data, and the changes were compared to evaluate the effectiveness of the ODI. The data collected before and after the ODI were analyzed, and it was found that the data were not normally distributed. The researcher used unary linear regression, linear regression, and Wilcoxon signed rank to validate the hypotheses. The results indicated that the students’ academic self-efficacy, perceived teacher support, peer relationship, learning engagement, and academic performance had significantly improved after the ODI. In conclusion, this study suggests that goal setting, feedback, coaching, team building, appreciative inquiry, and team activities are effective ODI for enhancing academic self-efficacy, perceived teacher support, and peer relationships. Furthermore, the study found that academic self-efficacy, perceived teacher support, peer relationship, and learning engagement positively correlate with academic performance.